1
$\begingroup$

Let $M$ be a finitely generated module over a ring $R$ and $\phi: M \rightarrow R^n$ be a surjective homomorphism. Show that the $\ker(\phi)$ is finitely generated submodule of $M$.

My effort: Since $M$ is finitely generated, So there exist $x_1,x_2, \ldots, x_k \in M$ such that $M = \langle x_1,x_2, \ldots, x_k \rangle = Rx_1 + Rx_2 + \cdots +Rx_k$. Since $\phi$ is surjective so, $\langle\phi(x_1), \cdots, \phi(x_k) \rangle = R^n$. By first isomorphism theorem, $M/\ker(\phi) \cong R^n$. And $R^n$ is finitely generated so $M/\ker(\phi)$ is finitely generated. We also have the following exact sequence $0 \rightarrow \ker(\phi) \rightarrow M \rightarrow M/\ker(\phi) \rightarrow 0$.

I am stuck after this point. Any help would be appreciated! Thanks in advance!

$\endgroup$
2
$\begingroup$

One way of seeing this is that since $M/\ker(\phi) \simeq R^n$, this is a free module, and thus the projection $M \rightarrow M/\ker(\phi)$ is a retraction, and therefore $\ker(\phi)$ is a direct summand of $M$:

$$ M = \ker(\phi) \oplus S $$

for some submodule $S$. In particular, there exists $y_i \in \ker(\phi), s_i \in S$ for each $i$ such that

$$ x_i = y_i + s_i $$

Now I claim that $\ker(\phi) = \langle y_1 ,\dots,y_k\rangle$. In effect, let $y \in \ker(\phi)$. Now

$$ y = \sum_{1 \leq i \leq k}a_ix_i = \sum_{1 \leq i \leq k}a_i s_i + \sum_{1 \leq i \leq k}a_iy_i $$

but since $y - \sum_{1 \leq i \leq k}a_iy_i = \sum_{1 \leq i \leq k}a_is_i \in \ker(\phi)\cap S = \{0\}$,

$$ y = \sum_{1 \leq i \leq k}a_iy_i $$

$\endgroup$
  • $\begingroup$ It makes perfect sense! Thanks! $\endgroup$ – Shubham Namdeo Jul 3 '18 at 4:58

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.